First observations of geophagy for two neotropical passerines species - Willrich, Guilherme; Maciel Brüggemann, Fernando (Acta Biológica Catarinense, 2026)
Geophagy is the consumption of soil, clay or sediments by animal species. In birds, this behaviour was documented to only 2% of the world’s avifauna and several bird families lack evidence of geophagy. Here we present the first report of geophagy for the Parulidae family and only the fourth for Thraupidae, related to the species Tropical Parula (Setophaga pitiayumi) and Faw-breasted Tanager (Pipraeidea melanonota), respectively. We speculate that the observed behaviour could be related to mechanical digestion, protection against toxic food compounds or even mineral supplementation.